2006
DOI: 10.31887/dcns.2006.8.1/ldelisi
|View full text |Cite
|
Sign up to set email alerts
|

Understanding structural brain changes in schizophrenia

Abstract: Schizophrenia is a chronic progressive disorder that has at its origin structural brain changes in both white and gray matter. It is likely that these changes begin prior to the onset of clinical symptoms in cortical regions, particularly those concerned with language processing. Later, they can be detected by progressive ventricular enlargement. Current magnetic resonance imaging (MRI) technology can provide a valuable tool for detecting early changes in cortical atrophy and anomalous language processing, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(15 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…The initiatives taken to pharmacologically enhance cognition are plentiful; however, the results of such studies are diverse and few studies have been able to demonstrate replicable cognitive enhancement in patients with schizophrenia [ 38 ]. One contributing factor to these shortcomings, may be that schizophrenia encompasses abnormal progressive loss in brain volume [ 41 ], possibly counteracting any cognitive enhancing potential. However, cognitive enhancing therapy was recently demonstrated to counteract gray matter loss in patients with schizophrenia [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initiatives taken to pharmacologically enhance cognition are plentiful; however, the results of such studies are diverse and few studies have been able to demonstrate replicable cognitive enhancement in patients with schizophrenia [ 38 ]. One contributing factor to these shortcomings, may be that schizophrenia encompasses abnormal progressive loss in brain volume [ 41 ], possibly counteracting any cognitive enhancing potential. However, cognitive enhancing therapy was recently demonstrated to counteract gray matter loss in patients with schizophrenia [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“… 40 Thompson and colleagues 41 have also reported an accelerated decrease in gray matter volume in early-onset schizophrenia. Of particular note, in a recent review of the literature, DeLisi et al 42 reviewed evidence for progressive changes in both chronic and first-episode patients. They concluded that progressive changes over time in chronic patients are far less than what is observed in first-episode patients, again underscoring the fact that progressive changes in the early stages of illness may be more dramatic than changes observed later in the course of the illness.…”
Section: Mri Findings In Schizophreniamentioning
confidence: 99%
“…Schizophrenia is a complex disorder that includes widespread neurocognitive 1 , 2 and neuroanatomical impairments 3 , 4 . Studies have shown that compared to healthy controls, schizophrenia patients (SZH) have impaired cognitive performance across all cognitive domains including processing speed 5 , attention and vigilance 6 , working memory 7 , verbal learning 8 , visual learning 9 , reasoning/problem solving 9 , and social cognition 10 .…”
Section: Introductionmentioning
confidence: 99%